Developing a web-based online counseling service application - Ahmad Miftah; Farida Aryani; Arnidah Arnidah; Muhammad Anas; Abdul Saman (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
The purpose of this study was to produce a website-based online counseling service application for guidance and counseling students and teachers at SMK Telkom Makassar. The approach of this research is R&D/Research and Development. This research was conducted through seven main stages, namely, (1) Initial research and information gathering, (2) Planning, (3) Preparation of the initial model format, (4) conducting an early stagetrial, (5) revise the main model, (6) conduct a field trial of the main model, (7) revise the operational model. Testing of application products that are validated by 1 material expert and 1 expert on the distribution of learning media that has been developed. The method used to analyze the data is a quantitative descriptive analysis technique with a predetermined score distribution and scale category. The results of the validation of the learning media are: (1) The material expert assesses that it is very feasible with a percentage of (88.88%). (2) Media experts considered it very feasible with a percentage of (79.1%). Based on these results, the online counseling service application that has been developed is suitable for use in providing counseling services at SMK Telkom Makassar.